Pricing methods in outcome-based contracting: δ1: cost effectiveness analysis and cost-utility analysis-based pricing. (1st November 2020) - Alkhatib, Nimer S.; Ramos, Kenneth; Erstad, Brian; Slack, Marion; McBride, Ali; Bhattacharjee, Sandipan; Abraham, Ivo
Abstract: Aims: Six Delta is a six-dimensional independent platform for outcome-based pricing/contracting. The first dimension (δ1) estimates prices on the basis of cost-effectiveness (CEA) and cost-utility analysis (CUA). We describe this dimension's methodology and present a proof-of-concept application to the treatment of non-small cell lung cancer (NSCLC) with EGFR mutation with osimertinib. Materials and methods: CEA and CUA were performed using established methods. Probabilistic sensitivity analyses (PSA) were performed to generate cost-effectiveness acceptability curves (CEAC), specifically the PSA incremental cost-effectiveness (PSA ICER) and incremental cost-utility ratio generated CEACs (PSA ICUR). Price of treatment was estimated at three certainty levels (0%, turning point%, 100%). The marketed drug price at turning point was used to estimate prices at 0% and 100% certainty levels, as per PSA ICER and PSA ICUR-generated CEACs. The resulting prices were pooled, inflated, and simulated by Monte Carlo Simulation (MCS) methods to estimate the dimension-specific price based on CEA and CUA (DSPCEA/CUA ). A proof-of-concept exercise with osimertinib in NSCLC was performed for two hypothetical outcome-based contracts: 1-year (2019–2020) and 2-years (2019–2021). Results: Turning points were estimated at the 50% certainty level in both PSA ICER and ICUR-generated CEACS. At these points, the wholesale acquisition cost for osimertinib was $14, 616 (30-day prescription); inflated by 0.44% for 1-year and by 0.72% for 2-year contracts. Additional prices at 0% and 100% certainty levels were quantified based on the PSA ICER and ICUR-generated CEACs. The MCS yielded a DSPCEA/CUA of $16, 391 for the 1-year contract and a DSPCEA/CUA at $16, 677 for the 2-year contract for a 30-day prescription. Conclusions: We demonstrated that conventional CEA and CUA methods generate price estimates at varying levels of certainty that can be integrated into our proposed Six Delta platform for outcome-based pricing/contracting.